Hubungan Antara Toxic Parenting Dengan Relationship Commitment Pada Dewasa Awal - Hutapea, Yohana; Kusumiati, Ratriana Yuliastuti Endang (Pascasarjana STIE Amkop Makassar, 2025)
Early adulthood is a crucial stage in a person's life journey. Besides being at the peak of physical condition, individuals at this age also tend to have a stable personality that does not change significantly. The family is one of the most fundamental constructs of human relationships and has a significant impact on a person's life. In a family, parenting serves as a way to raise and educate children by teaching them everything related to adult life. Toxic parenting has become a prevalent phenomenon in our society today. Toxic parenting refers to an inappropriate parenting style that can have negative impacts on children. It occurs when parents fail to treat their children according to their individual needs. Parents with toxic parenting tendencies are often unwilling to show respect, compromise, or treat their children with kindness. They believe they are always right and focus solely on their own desires without considering the needs of their children. Kata Kunci: Toxic parenting, relationship commitment,Dewasa awal.